A Proposed Framework to Improve the Ranking of Syrian Universities (Damascus University Journal for the economic and Political sciences, 2022)
This research aims to develop a proposed framework to improve the ranking of Syrian universities, thus contributing to the creation of a motivating mechanism that pushes Syrian universities to compete with each other, which helps to continuously improving their performance level. The proposed framework included seven main fields: teaching, scientific research, prizes, university income, international orientation, the university’s academic presence on the Internet, and the reputation of the university with employers. The standards for this framework were presented for evaluation by an expert sample of faculty members, which included 183 individuals, from various Syrian universities. The standards included in the fields of the proposed framework were appropriate for the ranking of Syrian universities, from the point of view of the research sample members. However, the evaluation degrees given by the research sample to these fields varied. University’s reputation with employers received the highest evaluation, followed by the field of teaching, then the field of scientific research. The field of academic presence of the university on the Internet came next and then the field of university income, followed by the field of prizes, and finally the field of international orientation.
Keywords: proposed framework; universities ranking; Syrian universities